The prevalence of house dust mite (HDM) allergy and the use of HDM-impermeable bed covers in a primary care population of patients with persistent asthma in the Netherlands - de Vries, M.P. (Prim Care Respir J, 2005)
BACKGROUND: House dust mite (HDM) allergen is one of the most common allergens to which asthma patients are sensitised. Prevalence of HDM allergy varies in the literature. Use of HDM-impermeable bed covers reduces exposure to HDM allergen. The aim of this study was to assess the prevalence of HDM allergy in a primary care population of asthma patients, as well as the use of HDM-impermeable bed covers by these patients. METHODS: A random sample of asthma patients between 16 and 60 years old was taken from general practices. Allergy was assessed with a radio allegro sorbent test (RAST). A questionnaire was used to identify demographic characteristics and the actual use of bed covers. RESULTS: 534 patients were invited and 160 patients participated. 53 patients not willing to participate were randomly selected to test the external validity of our findings. The sample was representative for the primary care asthma population. 48.8% of the asthma population was sensitised to HDM allergen. 25.6% of the HDM-allergic asthma patients were using HDM-impermeable bed covers. CONCLUSION: Almost half of the patients with asthma were sensitised to HDM allergen. Only a minority of the patients used HDM-impermeable bed covers.